Fabrication of silver chalcogenolate cluster hybrid membranes with enhanced structural stability and luminescence efficiency. Issue 97 (20th November 2019) - Wang, Yi-Man; Zhang, Jiang-Wei; Wang, Qian-You; Li, Hai-Yang; Dong, Xi-Yan; Wang, Shan; Zang, Shuang-Quan
Abstract : We fabricated a silver cluster hybrid membrane for the first time, which significantly enhanced the structural stability and luminescence efficiency compared with discrete silver clusters. Abstract : The present study reports the fabrication of a silver chalcogenolate cluster hybrid membrane (SCC membrane) through self-assembly of SCCs, and then covalent cross-linking of the modified SCC assembled materials. This strategy provides access to silver clusters with superior chemical stability and enhanced luminescence efficiency for practical applications.